On Tethering Atonement Concepts to Scripture: Retribution, Propitiation, Passover, and Sacrifice - Rutledge, Jonathan (Philosophia Christi, 2025)
Alasdair MacIntyre once imagined a dystopian world in which the scientific community had been destroyed but where the language of science had persisted (albeit with terms that were no longer tethered to their richer, historical meanings). In this paper, I argue that William Lane Craig's atonement theology faces a similar issue: his use of key concepts - retribution, propitiation, Passover, and sacrifice - lacks sufficient tethering to the biblical texts, resulting in a distorted overarching theological framework. Along the way, I offer an alternative account of such concepts which, to my mind, aligns more closely with the witness of Scripture.